Solubility Controlling Peptide Tags of Opposite Charges Generate a Bivalent Immune Response Against Dengue ED3 Serotypes 3 and 4 - Rahman, Nafsoon; Miura, Shiho; Okawa, Mami; Kibria, Md. Golam; Islam, Mohammad Monirul; Kuroda, Yutaka (Frontiers in Immunology, 2021)
We previously demonstrated that a protein’s immunogenicity can be substantially increased by attaching hydrophobic solubility-controlling peptide tags (SCP-tags) producing small sub-visible aggregates. Here, we report oligomerization of Dengue envelop protein domain 3 (ED3), and consequently its immunogenicity, increase by mixing ED3s attached with SCP-tags of opposite charges at equimolar concentrations. We used ED3 serotype 3 (D3ED3) and 4 (D4ED3), which are, moderately and poorly immunogenic, respectively, and their SCP-tagged variants, constructed either by attaching a C-termini 5-Aspartic acid (C5D) or a 5-Lysine (C5K) tag. Light scattering indicated that the isolated tagged ED3s remained monomeric, but mixing the C5D and C5K tagged ED3s at equimolar concentration generated sub-visible aggregates of ~500 nm through electrostatic interaction. In addition, the oligomerized ED3s remained in a native-like state, as assessed by fluorescence spectroscopy and circular dichroism. In vivo immunogenicity of the D3ED3 and D4ED3 oligomers generated by the charged tags increased by 5 and 16 fold, respectively. Furthermore, injection of heterotypic ED3 oligomers (D3C5D+D4C5K) induced an immune response against both D3ED3 and D4ED3 in 3 of 4 responsive mice. Moreover, the IgG titer of the bivalent antigen D3C5D+D4C5K was over 100 times stronger than that generated by co-injecting untagged D3ED3 and D4ED3 (D3+D4). Altogether, these observations suggest that SCP-tags can provide a platform for producing a long-sought tetravalent dengue vaccine.